Mycobacterium tuberculosis PPE18 Protein Bodies in Insect Cells: A Candidate Tuberculosis Vaccine - Pu Wang; Gang Zhang; Yurong Cai; Lingling Jiang; Xiaoxia Niu; Sinong Zhang; Weifeng Gao; Zhiwei Wu; Yong Li (Vaccines)
Background/Objectives: Mycobacterium tuberculosis is the causative agent of tuberculosis and the leading cause of death from a single infection with the microorganism. Tuberculosis remains globally one of the major diseases leading to high mortality rates, with serious implications for public health and economic development. Therefore, tuberculosis prevention and control is crucial for global health and socio-economic stability. The development of effective preventive vaccines remains an urgent task in the fight against tuberculosis. Methods: The Mycobacterium tuberculosis antigen PPE18 was fused to Zera, and Bacmid was extracted and transfected into Sf9, which was purified and characterized for the formation of nanoparticle protein bodies. BALB/c mice and calves were immunized, and the immunogenicity of the nanoparticle vaccine was assessed by serum antibodies and splenic lymphocytes. Results: Zera-71CA-mCherry can be expressed in Sf9 cells, forming 0.5–1.2 μm protein bodies. Excising the mCherry sequence, Zera-71CA/Zera-PPE18 candidate nanoparticle-immunized mice were able to elicit serum antibody levels and the proliferation of splenic lymphocytes, and immunized calves were determined to have high levels of serum antibody levels, and IFN-γ and TNF-α levels. Conclusions: The results indicated that Zera-71CA/Zera-PPE18 recombinant nanoparticles had good immunogenicity as a subunit vaccine in both BALB/c mice and calves and are potential candidates for further development as effective subunit vaccines.